A convergent FV–FE scheme for the stationary compressible Navier–Stokes equations. (19th May 2020) - Perrin, Charlotte; Saleh, Khaled
Abstract: In this paper we prove a convergence result for a discretization of the three-dimensional stationary compressible Navier–Stokes equations assuming an ideal gas pressure law p(ρ )=a ρ ^γ with γ> 32 . It is the first convergence result for a numerical method with adiabatic exponents γ less than 3 when the space dimension is 3. The considered numerical scheme combines finite volume techniques for the convection with the Crouzeix–Raviart finite element for the diffusion. A linearized version of the scheme is implemented in the industrial software CALIF 3 S developed by the French Institut de Radioprotection et de Sûreté Nucléaire.